Targeted locus amplification to develop robust patient-specific assays for liquid biopsies in pediatric solid tumors - van Zogchel, Lieke M. J.; Lak, Nathalie S. M.; Gelineau, Nina U.; Sergeeva, Irina; Stelloo, Ellen; Swennenhuis, Joost; Feitsma, Harma; van Min, Max; Splinter, Erik; Bleijs, Margit; Groot Koerkamp, Marian; Breunis, Willemijn; et al. (Frontiers in Oncology, 2023)
Background: Liquid biopsies combine minimally invasive sample collection with sensitive detection of residual disease. Pediatric malignancies harbor tumor-driving copy number alterations or fusion genes, rather than recurrent point mutations. These regions contain tumor-specific DNA breakpoint sequences. We investigated the feasibility to use these breakpoints to design patient-specific markers to detect tumor-derived cell-free DNA (cfDNA) in plasma from patients with pediatric solid tumors. Materials and methods: Regions of interest (ROI) were identified through standard clinical diagnostic pipelines, using SNP array for CNAs, and FISH or RT-qPCR for fusion genes. Using targeted locus amplification (TLA) on tumor organoids grown from tumor material or targeted locus capture (TLC) on FFPE material, ROI-specific primers and probes were designed, which were used to design droplet digital PCR (ddPCR) assays. cfDNA from patient plasma at diagnosis and during therapy was analyzed. Results: TLA was performed on material from 2 rhabdomyosarcoma, 1 Ewing sarcoma and 3 neuroblastoma. FFPE-TLC was performed on 8 neuroblastoma tumors. For all patients, at least one patient-specific ddPCR was successfully designed and in all diagnostic plasma samples the patient-specific markers were detected. In the rhabdomyosarcoma and Ewing sarcoma patients, all samples after start of therapy were negative. In neuroblastoma patients, presence of patient-specific markers in cfDNA tracked tumor burden, decreasing during induction therapy, disappearing at complete remission and re-appearing at relapse. Conclusion: We demonstrate the feasibility to determine tumor-specific breakpoints using TLA/TLC in different pediatric solid tumors and use these for analysis of cfDNA from plasma. Considering the high prevalence of CNAs and fusion genes in pediatric solid tumors, this approach holds great promise and deserves further study in a larger cohort with standardized plasma sampling protocols.